Shirt sponsorship by gambling companies in the English and Scottish Premier Leagues: global reach and public health concerns. (18th August 2019) - Bunn, Christopher; Ireland, Robin; Minton, Jonathan; Holman, Daniel; Philpott, Matthew; Chambers, Stephanie
Abstract: While the nature of gambling practices is contested, a strong evidence base demonstrates that gambling can become a serious disorder and have a range of detrimental effects for individuals, communities and societies. Over the last decade, football in the UK has become visibly entwined with gambling marketing. To explore this apparent trend, we tracked shirt sponsors in both the English and Scottish Premier Leagues since 1992 and found a pronounced increase in the presence of sponsorship by gambling companies. This increase occurred at the same time the Gambling Act 2005, which liberalized rules, was introduced. We argue that current levels of gambling sponsorship in UK football, and the global visibility it provides to gambling brands, is a public health concern that needs to be debated and addressed. We recommend that legislators revisit the relationship between football in the UK and the sponsorship it receives from the gambling industry.